2002
DOI: 10.1038/sj.ejhg.5200875
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BMP4 and its specific inhibitor NOG as candidates in human neural tube defects (NTDs)

Abstract: Neural tube defects (NTD) are among the most common congenital malformations in humans. The current view is that there are no major genes causing NTDs, but combinations of sequence variants in different genes have additive effects on determining the malformation. Therefore it is important to identify such sequence variants to get a better understanding of NTD pathogenesis. Studies on animal models have shown that BMP4 and NOG are involved in the patterning of the neural tube. We therefore performed a single-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Moreover, BMP4 treatment promoted postnatal differentiation of cerebellar neurons (Angley et al, 2003). Studies on animal models have shown that BMP4 is involved in the patterning of the neural tube; missense mutations in BMP4 were found in spina bifida aperta patients (Felder et al, 2002). The increased expression of PIGS, KLF7, and BMP4 was confirmed by real‐time RT‐PCR experiments and was induced selectively by CCL5 but not by CXCL12 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BMP4 treatment promoted postnatal differentiation of cerebellar neurons (Angley et al, 2003). Studies on animal models have shown that BMP4 is involved in the patterning of the neural tube; missense mutations in BMP4 were found in spina bifida aperta patients (Felder et al, 2002). The increased expression of PIGS, KLF7, and BMP4 was confirmed by real‐time RT‐PCR experiments and was induced selectively by CCL5 but not by CXCL12 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of these factors may determine the incidence and severity of the CNS malformations. Mutations in genes involved in dorso-ventral patterning of the NT like BMP-4, Nog, Pax3, Six3 or Shh are known to be associated with various NT malformations in humans [5][6][7][8][9]. Reported environmental causes include physical agents, therapeutic drugs, chemicals or infectious agents [4,10].…”
Section: Introductionmentioning
confidence: 97%
“…In rare cases, syndromes that variably present with NTDs have been associated with a mutation in a single gene (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Using traditional linkage disequilibrium, patient studies of individual (non-folate-related) candidate genes, including jumonji (JMJ) (37), apolipoprotein E (ApoE), apolipoprotein B (ApoB) (38), bone morphogenetic protein-4 (BMP4) (39), CITED2 (40), transcription factor AP2 (TFAP2) (41), multiple sequence homeobox-2 (MSX2) (41), PAX3 (42) and noggin (NOG) (43), have only rarely succeeded in ascribing attributable risk for NTDs to specific genes.…”
Section: Introductionmentioning
confidence: 99%